A theoretical model for bubble formation during horizontal gas injection into liquid flow in vertical tubes. Issue 10 (3rd October 2018) - Huang, Qian; Li, Changjun
ABSTRACT: Bubble formation in flowing liquid is an important process for wastewater treatment, processing of molten metals, and biological processes. Based on a global balance of force on the bubble, this report describes a new theoretical model for bubble formation during horizontal gas injection into turbulent liquid flow in a vertical tube. This work highlights the importance of choosing the correct drag law in accordance with the bubble size. Five models for drag coefficient are compared, and of these, model III is recommended. Modified detachment criteria are applicable, depending on the liquid velocity. The new analytical model yields good predictions compared with experimental data. Based on the theoretical model, this study investigates the effects of the direction of liquid flow, liquid velocity, gas velocity, and orifice diameter on the bubble formation behavior. GRAPHICAL ABSTRACT: